Controls on cave drip water temperature and implications for speleothem-based paleoclimate reconstructions. (1st November 2015) - Rau, Gabriel C.; Cuthbert, Mark O.; Andersen, Martin S.; Baker, Andy; Rutlidge, Helen; Markowska, Monika; Roshan, Hamid; Marjo, Christopher E.; Graham, Peter W.; Acworth, R. Ian
Abstract: While several studies explore cave climate and thermal regimes, little is known about the controls on cave drip water temperature. Yet water temperature significantly influences biogeochemical processes associated with cave drips. To identify the processes that control the cave drip water temperature, we measured the temperatures at multiple locations along a speleothem flow path and drip sources (stalactites) concurrently with the drip rates in Cathedral Cave, Wellington, Australia. We monitored long-term drip water temperature, drip rates, surface and cave climate and in-cave evaporation rates and conducted 3 infiltration experiments with different flow, temperature and isotopic conditions. Our results show that the drip water temperature is controlled by multiple superimposed heat transport mechanisms that act upon the infiltrating water in the epikarst, the water film after it enters the cave and before it becomes a drip. The two main heat sources/sinks for drip water are the cave air and the surrounding rock. The subsurface temperature is coupled to the surface temperature by conduction through the soil and rock mass, but the cave climate is also coupled to the surface climate by venting. On a regional scale, drip temperatures are mainly driven by the annual ground surface temperature signal but damped with depth and shifted in time compared to the surface. On a local scale, the drip water temperature can differ significantly from cave air and speleothem temperature due to the latent heat exchange of evaporation and localised water film convection. The main controls are ground surface temperature, subsurface depth, air density induced ventilation, distance from entry and drip rate. We present a conceptual model that explains drip water temperature signals and provide signal driven guidance on best type and location for speleothem sampling. We anticipate that our results will significantly improve the understanding of temperature-dependent paleoclimate signals from speleothem archives. Highlights: Cave drip water temperature is controlled by multiple heat transfer mechanisms. The dynamic surface heating signal and the cave atmosphere are the two main drivers. Venting can cause significant and frequent evaporative cooling of cave drip water. We provide a conceptual model for the controls on cave drip water temperature. Signal based guidance on the type and location of speleothem for paleoclimate.